Predictors of a high incidence of opportunistic infections among HIV-infected children receiving antiretroviral therapy at Amhara regional state comprehensive specialized hospitals, Ethiopia: A multicenter institution-based retrospective follow-up study - Mekonnen, Gebrehiwot Berie; Birhane, Binyam Minuye; Engdaw, Melaku Tadege; Kindie, Wotetenesh; Ayele, Amare Demsie; Wondim, Amare (Frontiers in Pediatrics, 2023)
Introduction Globally, opportunistic infections are the leading causes of morbidity and mortality among HIV-infected children, contributing to more than 90% of HIV-related deaths. In 2014, Ethiopia launched and began to implement a “test and treat” strategy aiming to reduce the burden of opportunistic infections. Despite this intervention, opportunistic infections continue to be a serious public health issue, with limited evidence available on their overall incidence among HIV-infected children in the study area. Objective The study aimed to assess the incidence of opportunistic infections and to identify predictors of their occurrence among HIV-infected children receiving antiretroviral therapy at Amhara Regional State Comprehensive Specialized Hospitals in 2022. Methods A multicenter, institution-based retrospective follow-up study was conducted among 472 HIV-infected children receiving antiretroviral therapy at Amhara Regional State Comprehensive Specialized Hospitals from May 17 to June 15, 2022. Children receiving antiretroviral therapy were selected using a simple random sampling technique. Data were collected using national antiretroviral intake and follow-up forms via the KoBo Toolbox. STATA 16 was used for data analyses, and the Kaplan–Meier method was used to estimate probabilities of opportunistic infection-free survival. Both bi-variable and multivariable Cox proportional hazard models were employed to identify significant predictors. A P-value <0.05 was taken to indicate statistical significance. Results Medical records from a total of 452 children (representing a completeness rate of 95.8%) were included and analyzed in the study. The overall incidence of opportunistic infections among children receiving ART was 8.64 per 100 person-years of observation. The predictors of elevated incidence of opportunistic infections were: a CD4 cell count below a specified threshold [AHR: 2.34 (95% CI: 1.45, 3.76)]; co-morbidity of anemia [AHR: 1.68 (95% CI: 1.06, 2.67)]; ever having exhibited only fair or poor adherence to ART drugs [AHR: 2.31 (95% CI: 1.47, 3.63)]; never having taken tuberculosis-preventive therapy [AHR: 1.95 (95% CI: 1.27, 2.99)]; and not having initiated antiretroviral therapy within 7 days of HIV diagnosis [AHR: 1.82 (95% CI: 1.12, 2.96)]. Conclusion In this study, the incidence of opportunistic infections was high. Early initiation antiretroviral therapy has direct effect on boosting the immunity, suppressing viral replications and increases the CD4 count, so that the occurrence of opportunistic infection will reduce the incidence of OIs.